Anna DuBord: capstone - DuBord, Anna, artist (Colorado State University. Libraries, 2025)
The artist's statement: Throughout my practice, I've found myself grounded within materials and color pallets I find to be nostalgic, incorporating elements that many people might connect with through their own memories of childhood. I'm drawn to textures that allow for mistakes, and over time I've learned to follow where life nudges me rather than forcing a sense of control. Because of this, I gravitate towards processes that force me to be present within the work, instead of controlling every step. After all, life has a funny way of teaching you the lessons you need most. For me, it was allowing myself to let the little things go. The version of myself from five years ago is not the person I am today, and if I'm honest, when I look in the mirror, I hardly see her anymore. At a particularly rocky crossroad between these two versions of myself, something just clicked. My mind stopped running in overdrive, and I realized: it's not that serious. Yes, life has its hard parts, but it also has amazing ones and somehow, I hadn't been letting myself enjoy them. It was as if someone flipped a switch. Everything that once felt so overwhelming suddenly seemed smaller. And when those things got smaller, life itself got bigger. I'm privileged to experience these moments when pressure softens, order and chaos blur, and humor slips in unexpectedly. My work is about freedom. It’s about choosing where and how to place my energy. It's about acknowledging the absurdity of life and letting myself enjoy it more. Through each piece, I hope to create a space where people can breathe, let something go, and remember that things really aren't as serious as they seem. Guided by a spirit of play, I allow my practice to unfold with curiosity and openness.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing and jewelry